1975
DOI: 10.1152/jappl.1975.39.6.950
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal mucous transport in experimental canine asthma

Abstract: Tracheal mucous velocity (TMV) was measured in experimental canine asthma. All 10 sensitive dogs exposed to an aerosol of Ascaris suum extract showed a decrease in TMV to about one-third of base-line values within 45 min whereas only half of them (reactors) responded with bronchospasm as measured by a significant reduction in specific respiratory system conductance (SGrs). Mean TMV remained decreased at the end of the 2-h observation period when mean SGrs had returned to base-line values in the reactors. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is only recently that the aerosol route of administration has been explored with this compound. For example, it has been shown that an aerosol formulation of FPL before and during antigen challenge of dogs [9] or ragweed sensitive human patients 110], prevented antigen-induced decreases in tracheal mucous velocity. This response was shown to be indepen dent of anaphylactic bronchoconstriction, however.…”
Section: Introductionmentioning
confidence: 99%
“…It is only recently that the aerosol route of administration has been explored with this compound. For example, it has been shown that an aerosol formulation of FPL before and during antigen challenge of dogs [9] or ragweed sensitive human patients 110], prevented antigen-induced decreases in tracheal mucous velocity. This response was shown to be indepen dent of anaphylactic bronchoconstriction, however.…”
Section: Introductionmentioning
confidence: 99%
“…larger doses of ipratropium bro mide might have produced a fall in tracheal mucous velocity. Nevertheless, the doses of the drugs employed are those recommended from clinical studies which presumably would result in a similar degree of bronchodilatation in patients [12], Thus, these studies suggest that ipratropium bromide in thera peutic doses ought not to depress mucociliary transport.…”
Section: Discussionmentioning
confidence: 89%
“…Using an inhalation challenge model that used ragweed extract, Mezey et al [5] showed impairment in mucus transport in asymptomatic ragweed‐sensitive asthmatics both immediately and 1 h after challenge. Allergen challenge in animal models of allergic airways disease also shows decreased TMV for several days [6, 7, 30] with no clear linkage to the time course of bronchoconstriction in the animals. Thus, the observations presented in this report are consistent with earlier animal and human studies as well as those seen in naturally occurring disease.…”
Section: Discussionmentioning
confidence: 99%